How to manage endings in unsuccessful therapy: A qualitative comparison of youth and clinician perspectives - Bear, HA; Dalzell, K; Edbrooke-Childs, J; Garland, L; Wolpert, M (Taylor and Francis, 2021)
Background: Approximately half of those who access child and adolescent mental health services do not show measurable improvement in symptoms. This study aimed to provide practice recommendations for managing treatment endings, particularly when outcomes have not improved. Method: Semi-structured interviews were carried out with 26 young people with a history of anxiety and/or depression along with 7 roundtable sessions with 52 mental health clinicians. Data were analyzed using Framework Analysis. Results: A common experience for young people when outcomes did not improve was a poor experience of the treatment ending, which often resulted in setbacks in their mental health and feelings of loss and abandonment. Clinicians agreed that ending was hard for young people and reported that they found managing ending hard on a personal and professional level. This was compounded by unrealistically high public expectations about the impact of therapy on outcomes and trying to strike a balance between fostering hope and managing expectations, within a context of inflexible service structures and resource constraint. Implications: Recommendations include establishing expectations from the outset and a shared understanding of what outcomes matter most to the young person. This can be achieved through communicating honestly about likely outcomes, while also providing hope.